Perceptual pitch deficits coexist with pitch production difficulties in music but not Mandarin speech - Yang, Wu-xia; Feng, Jie; Huang, Wan-ting; Zhang, Cheng-xiang; Nan, Yun (Frontiers in Psychology, 2014)
Congenital amusia is a musical disorder that mainly affects pitch perception. Among Mandarin speakers, some amusics also have difficulties in processing lexical tones (tone agnosics). To examine to what extent these perceptual deficits may be related to pitch production impairments in music and Mandarin speech, 8 amusics, 8 tone agnosics, and 12 age- and IQ-matched normal native Mandarin speakers were asked to imitate music note sequences and Mandarin words of comparable lengths. The results indicated that both the amusics and tone agnosics underperformed the controls on musical pitch production. However, tone agnosics performed no worse than the amusics, suggesting that lexical tone perception deficits may not aggravate musical pitch production difficulties. Moreover, these three groups were all able to imitate lexical tones with perfect intelligibility. Taken together, the current study shows that perceptual musical pitch and lexical tone deficits might coexist with musical pitch production difficulties. But at the same time these perceptual pitch deficits might not affect lexical tone production or the intelligibility of the speech words that were produced. The perception-production relationship for pitch among individuals with perceptual pitch deficits may be, therefore, domain-dependent.